THE REQUIREMENTS FOR TEACHING ENGLISH LESSONS - Dr. Najm Abdullah Burhan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Most of the world's English language teachers speak English as second or third language rather than as their first language. for many their proficiency in teaching English may not reach benchmarks established by their employers, so they must need to know the requirements for teaching English in their classes, raising the issue that is the focus of this article, namely, what kind of teaching skills in English is necessary to be an effective teacher of English? The article seeks to provide an overview of the requirements for teaching English lessons and improve English teachers` proficiency. so it describe the kind of specialized English teaching skills needed to teaching English in classrooms, and explore the relationship between teaching ability and English language proficiency, considers the impact of language ability on different dimensions of teaching, and raises the implications for teaching skills in English language .